Does the severity of tissue eosinophilia of colonic neoplasms reflect their malignancy potential? - Şafak KIZILTAŞ; Saime SEZGİN RAMADAN; Ahmet TOPUZOĞLU; Sevgi KÜLLÜ (Turkish Journal of Gastroenterology, 2019)
-